1966
DOI: 10.1128/jb.92.6.1655-1662.1966
|View full text |Cite
|
Sign up to set email alerts
|

Production, Purification, and Composition of Staphylococcal α Toxin

Abstract: COULTER, JOHN R. (Institute of Medical and Veterinary Science, Adelaide, Australia); Production, purification, and composition of staphyloccocal a toxin. J. Bacteriol. 92:1655-1662. 1966-Pure staphylococcal a toxin has been prepared in quantities suitable for chemical, biological, and clinical characterization. Purification was achieved by acid-methanol precipitation, chromatography on G100 Sephadex, and electrophoresis in G100 Sephadex. We recovered 25% of the crude toxin in pure form, a yield of 12 mg/liter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1
3

Year Published

1970
1970
1979
1979

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
2
16
1
3
Order By: Relevance
“…Examination in the electron microscope confirmed the characteristic shape of the ferritin particles (Fig. 2,3,4).…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Examination in the electron microscope confirmed the characteristic shape of the ferritin particles (Fig. 2,3,4).…”
Section: Methodsmentioning
confidence: 70%
“…Anti-alpha gamma globulin. Several rabbits were injected with purified alpha toxin (3). The toxin was allowed to aggregate by standing at 4 C for several weeks, and the aggregate was suspended in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…A tendency to aggregate or associate with cellular material is apparently characteristic of several bacterial extracellular hemolysins or cytolytic toxins (11). Staphylococcal alphatoxin aggregates during purification to a larger, but still soluble, particle and can also polymerize to a water-insoluble protein (4,15,16). The F and S components of staphylococcal leukocidin both polymerize in low-ionic-strength solutions (48).…”
Section: Discussionmentioning
confidence: 99%
“…McNiven and Arbuthnott reported that less than 1% of the total hemolytic activity in Staphylococcus aureus strain Wood 46 is cell associated (11), suggesting that alphahemolysin is secreted rapidly without lag after synthesis. Recently, Coulter reported that alpha-hemolysin, as detected by ferritin-labeled antisera, is associated with the inner surface of the membrane (5). Using established protoplast fractionation techniques (14), we found that the cellular localization of alpha-hemolysin was almost exclusively in the periplasmic fraction of several strains of S. aureus.…”
mentioning
confidence: 82%
“…Extracellular staphylococcal alpha-hemolysin has been purified and characterized by many investigators (3,5,9). In contrast, information pertaining to the location and characteristics of cellular alpha-hemolysin is almost nonexistent.…”
mentioning
confidence: 99%